Time to scale is now-now: CGIAR-GIZ scaling networking and learning event - Schut, Marc; Pircher, Thomas (CGIAR System Organization, 2022)
On 22 November 2022, 34 CGIAR scaling experts and members of the GIZ Taskforce on Scaling came together in Nairobi, Kenya for a ‘scaling networking and learning event’. The group represented 8 CGIAR centres as well as the CGIAR System Organization, who were joined by representatives of the World Vegetable Centre, FAO, FCDO, GIZ FIA, Wageningen University, UC Davis, the USAID Horticulture Innovation Lab, and World Bank. Together, the scaling experts backstop 22 out of the 32 CGIAR Initiatives, in 57 countries, with several experts supporting the entire Initiative portfolio at a global level. This document is a 4-pager summary of key-takeaways from the scaling networking and learning event.